Plato in Poland 1800-1950 - Mróz, Tomasz (1975- ) (Baden-Baden: Academia)
The subject of this work, Plato`s reception in Poland, is not original, nor is it unknown in the research literature. Over one hundred years ago, the first text entitled Plato in Poland was published by Lewis Campbell, who enthusiastically reported on Wincenty Lutosławski`s studies on Plato.
Keywords: Plato (filozof; 427 p.n.e.-347 p.n.e.); recepcja; krytyka; interpretacja; Polska